ANALISIS HARGA POKOK PRODUKSI UNTUK MENENTUKAN HARGA JUAL PADA BE LIMA PRINTING & ADVERTISING - Ani Maslina; Nevia Benita Putri Asmarani; Tri Budi Purnaningtyas; Halleina Putri Rejeki Hartono (Cahaya Ilmu Bangsa, 2024)
This research analyze the calculation of the cost of production by implementing the job order costing method at the MSME Be Lima Printing & Advertising located in Madiun. This MSME operates in the printing and advertising sector, with a production system based on orders. Currently, the calculation of the cost of production is carried out simply and does not follow applicable accounting standards, so the selling price of the product only follows market prices and industry estimates. The research approach used is descriptive quantitative, collecting primary data through interviews and secondary data from company documents. The analysis is carried out by calculating various components of production costs, such as raw materials, direct labor and factory overhead costs. The research results show that the production cost for a 2x1 size banner is IDR 33,050 per unit, and for a 2x3 size banner it is IDR 95,822 per unit. Based on the job order costing method, the appropriate selling price is IDR 39,660 for size 2x1 and IDR 114,986 for size 2x3, which is higher than the selling price currently applied by the company. This research concludes that the application of the job order costing method can provide more accurate calculations of production costs and selling prices, helping Be Lima Printing & Advertising MSMEs in setting more precise selling prices in accordance with the desired profit targets..